(untitled) - Dershowitz, Alan M. (New Jersey, 2005)
In The Case for Peace, Dershowitz identifies twelve geopolitical barriers to peace between Israel and Palestine–and explains how to move around them and push the process forward. From the division of Jerusalem and Israeli counterterrorism measures to the security fence and the Iranian nuclear threat, his analyses are clear-headed, well-argued, and sure to be controversial. According to Dershowitz, achieving a lasting peace will require more than tough-minded negotiations between Israelis and Palestinians. In academia, Europe, the UN, and the Arab world, Israel-bashing and anti-Semitism have reached new heights, despite the recent Israeli-Palestinian movement toward peace. Surveying this outpouring of vilification, Dershowitz deconstructs the smear tactics used by Israel-haters and shows how this kind of anti-Israel McCarthyism is aimed at scuttling any real chance of peace.
Keywords: Arab-Israeli conflict,Xung đột Do Thái-Ả rập; Peace,Hoà bình; 1993-,1993-